Teoria da Alienação nos Manuscritos de Marx: uma análise do processo de alienação e sua superação - Monserrat, José (2022)
The theory of alienation of the Economic-Philosophical Manuscripts (Marx, 2015a) is investigated focusing on the two transitions, the alienation process and its overcoming. The term alienation (Leopold, 2018) and the Manuscripts (Musto, 2014, 2019) are contextualized. The four steps of alienation are analyzed. In the first transition, the process of abstraction from exchange, private property, labor and capital is examined as process of alienation in the constitution of capitalism. Marx's homology between the process of abstraction of Hegel's dialectic and the process of abstraction of the alienation of man is analyzed. The controversies about homology are evaluated, and their origin is identified in Marx's critique of Hegel's dialectic. His main criticism: the abstract and alienated character of Hegel's dialectical overcoming, which reaffirms the alienation of man. Some criticisms of Marx's critique are evaluated and his “confusion” between pure and objective thoughts is analyzed, and his transforming perspective of society is highlighted. Three homologies are examined in the Manuscripts, by Klein (2015), Iber (2018) and Bavaresco et al (2019), which help to explain the problems of the first transition, and which are related to the negative anthropology of Marx's presupposed man, who is not subject of history (Fausto, 2015). In the second transition, the five steps of communism described in the Manuscripts are investigated. The first two expose the objective dimension of the reappropriation of the object by the workers, and the last three the subjective dimension of that reappropriation. The problem of the justification of the human essence is examined (Brudney, 1998). Workers are unaware of their human essence and are unable to assume it in practice. This does not represent a problem for Marx. His theoretical solution is carried out in practice. However, Feuerbach's self-certifying perception cannot be used as workers are objectively alienated. The revolutionary organization and practice of workers are insufficient to change their posture. It is not possible for workers to assume the communist vision – the subjective dimension of the reappropriation of the object – without realizing the objective dimension of the reappropriation. The objective and subjective dimensions must occur together. An example of revolution is examined in the Manuscripts, and it is concluded that revolution plays an indispensable role: it breaks the blockage of the objective dimension of alienation and allows the union of the objective and subjective dimensions of the reappropriation of the object, in which workers at last become conscious; it takes on a crucial role because, in capitalism, man is not a subject, he is a presupposition; propitiates the birth of man as subject of history. Two problems of the second transition are analyzed: the dependence of Marx's solution on the revolution, and the apparent impossibility of theorizing the overcoming of alienation, unless realizing it. Marx's theory does not convincingly explain how alienation is reproduced in capitalism, or it is overcome to build an emancipated society. This arises from his inadequate appropriation of the concept of human essence and of the Hegelian dialectical logic, which steers the process of alienation and its overcoming.